Answer:
xy+2x+3y+6=xy-5 .............(1)
xy-3x+2y-6=xy.....,.,(2)
2x+3y=-11
-4x+2y=6
first equation multiply by 2
(2)*(2x+3y)=-11
4x+6y=-22
-4x+2y=6
8y=-16 y=(-2),,,,, x=(-2,5)
Answer:
x
=
37
/8
Step-by-step explanation:
Answer:
when x=1
3x+5.=3×1+5=8
when x=0
3x+5.=3×0+5=5
Step-by-step explanation:
when x=-1
3x+5.=3×-1+5=-3+5=2
Answer:
answer a
Step-by-step explanation: cause it will equal up and it has to be negitive on answer so u divided it and youll get a
Answer:
-499,485.
Step-by-step explanation:
We can transform this to an arithmetic series by working it out in pairs:
6^2 - 7^2 = (6-7)(6+7) = -13
8^2 - 9^2 = (8-9)*8+9) = -17
10^2 - 11^2 = -1 * 21 = -21 and so on
The common difference is -4.
The number of terms in this series is (998 - 6) / 2 + 1
= 992/2 + 1 = 497.
Sum of n terms of an A.S:
= n/2 [2a1 + (n - 1)d
Here a1 = -13, n = 497, d = -4:
Sum = (497/2)[-26 - 4(497-1)]
= 497/2 * -2010
= -499,485.